PROPOSAL DESIGN AND RISK MANAGEMENT ASSESSMENT FOR UMKM PT. XYZ PERIOD 2023 - 2024 - Nadhief Fadlurrahman; Aries Heru Prasetyo (Jurnal Ekonomi, 2023)
PT XYZ is a company based in the bustling city of Jakarta. Recognized for its expertise in providing consultations and assessments to HRs and schools in the surrounding area. The firm has a reputation for its comprehensive and tailored solutions. The company is classified as a Micro, Small, and Medium Enterprise (UMKM) due to its annual income below IDR 2 billion. With the aim of bolstering the company's resilience and fortifying its operations, this study takes on the task of assisting PT XYZ in implementing a risk management solution that is both effective and efficient. By identifying and addressing potential risks, the company can navigate uncertainties and proactively mitigate threats. Upon conducting a thorough assessment, a total of 21 risks were identified, each presenting unique challenges to the company's stability. Among these risks, 9 were classified as very high risks, 10 as high risks, and 2 as medium risks. It became evident that immediate attention was required to avoid potential losses and problems that could impede the company's progress. To address these risks, a series of proactive and strategic solutions were advised. Each solution is carefully tailored to mitigate the specific risks and enhance the company's overall risk management framework. By implementing these recommendations, PT XYZ can minimize the likelihood and impact of potential disruptions, safeguarding its assets, reputation, and long-term sustainability. The proposed risk management solutions encompass a wide range of measures, including the establishment of robust internal controls, the implementation of comprehensive training programs, and the adoption of cutting-edge technological solutions. These measures, when integrated into the company's existing operations, will empower PT XYZ to proactively identify, assess, and respond to risks, thereby ensuring the continuity of its services and operations.